Effect of peak intensity periods on temporary fatigue and recovery kinetics in professional male football - Leifsson, E. N.; Krustrup, P.; Mohr, M.; Randers, M. B. (Journal of Sports Sciences, 2024)
We analysed peak 1-, 2- and 5-min periods and the associated 5-min recovery period in matches from three consecutive seasons in the Danish Superliga. A semi-automatic multicamera system was used to collect high-speed running distance (=5.5 m/s; HSRD), sprint distance (=7.0 m/s; SpD) and distance covered during intense acceleration (=3 m/s2; AccD). Analysis included 479 players and 6042 to 9671 match observations using rolling average. Distances covered per minute during the peak periods were significantly higher than match averages: HSRD (207-772%), SpD (447-1793%), and AccD (383-1096%). Distances covered per min were lower during 1-min recovery periods than match average for HSRD following peak 1-, 2- and 5-min period (29%, 6%, 3%, 2%, 2%; 35%, 11%, 0%, 2%, 3%; and 45%, 29%, 13%, 8%, 4%; p < 0.05, respectively), and for SpD (20%, 3%, 7%, 3% (4% higher in the 5th min); 24%, 12%, 3%, 0%, 7%; and 39%, 29%, 18%, 17%, 12%; p < 0.05, respectively). Opposite, AccD increased in the following 1-min recovery periods following peak 1-, 2- and 5-min periods (68%, 89%, 94%, 88%, 90%; 47%, 86%, 93%, 90%, 88%; 23%, 56%, 76%, 85%, 87%; p < 0.05) compared to match averages. Intensity was higher during shorter periods, whereas performance decrements were largest after longer peak periods for HSRD and SpD, whereas no decrement was observed in AccD.